The Social Dynamics of Communal Violence in India - Eckert, Julia (International Journal of Conflict and Violence (IJCV), 2009)
This article analyses mobilization among Hindu nationalist organizations. Rather than seeking their attraction in their discursive outputs and the possible answers they might give in times of change, the contention is that this is to be sought in the specific internal dynamics and the possibilities they create within their historical context. These specific opportunities for action are inherent firstly in a mode of operation relying on participation and involvement, their direct intervention, localness, and accessibility. The dichotomization inherent in violence makes it possible to integrate different interests and discontents under a single banner and therefore contributes to the project of unification undertaken by Hindu nationalism.